Stability Indicating RP-UPLC Method Development & Validation for Quantitation of Doravirine in Tablet Formulation (Journal of Pharmaceutical Negative Results, 2023)
The goal of this study is to provide a simple, accurate, and precise stability indicating technique for quantifying doravirine (DRVN) in tablet dosage form using UPLC. Chromatography was executed on an HSSC18 (100 mm x 2.1 mm, 1.8mm) reverse phase column with an isocratic elution of buffer acetonitrile, methanol and 0.01 N Potassium dihyrogen orthophosphate (pH-4.5) in the composition of 40:25:35% V/V at a flowing rate of 0.30ml/min. The column oven temperature was kept at 30.0°C, as well as the wavelength detection was processed at 238 nm. Retention time of DRVN was found to be 0.91min. Repeatability of the method was determined in the form of %RSD and the value was 0.33. The percentage mean recovery of the method was found to be 99.57%. LOD, LOQ values obtained from regression equation of DRVN were 0.71 and 2.31 mg/ml respectively. Regression equation and correlation coefficient values of DRVN were y = 17003x + 7203.1 and 0.9997. Drug was subjected for acid, peroxide, photolytic, alkali, neutral and thermal degradation study and the results shown that the percentage of degradation was found between 6.12% and 8.96%. Retention time and total run time of the drug was decreased and the developed method was simple and economical. So, the developed method can be adopted in industries as a regular quality control test for the quantification of DRVN.